Real-life chromoendoscopy for neoplasia detection and characterisation in long-standing IBD. Issue 1 (9th September 2016) - Carballal, Sabela; Maisterra, Sandra; López-Serrano, Antonio; Gimeno-García, Antonio Z; Vera, María Isabel; Marín-Garbriel, José Carlos; Díaz-Tasende, José; Márquez, Lucía; Álvarez, Marco Antonio; Hernández, Luis; De Castro, Luisa; Gordillo, Jordi; et al.
Abstract : Objective: Outside clinical trials, the effectiveness of chromoendoscopy (CE) for long-standing IBD surveillance is controversial. We aimed to assess the effectiveness of CE for neoplasia detection and characterisation, in real-life. Design: From June 2012 to 2014, patients with IBD were prospectively included in a multicentre cohort study. Each colonic segment was evaluated with white light followed by 0.4% indigo carmine CE. Specific lesions' features were recorded. Optical diagnosis was assessed. Dysplasia detection rate between expert and non-expert endoscopists and learning curve were ascertained. Results: Ninety-four (15.7%) dysplastic (1 cancer, 5 high-grade dysplasia, 88 low-grade dysplasia) and 503 (84.3%) non-dysplastic lesions were detected in 350 patients (47% female; mean disease duration: 17 years). Colonoscopies were performed with standard definition (41.5%) or high definition (58.5%). Dysplasia miss rate with white light was 40/94 (57.4% incremental yield for CE). CE-incremental detection yield for dysplasia was comparable between standard definition and high definition (51.5% vs 52.3%, p=0.30). Dysplasia detection rate was comparable between expert and non-expert (18.5% vs 13.1%, p=0.20). No significant learning curve was observed (8.2% vs 14.2%, p=0.46). Sensitivity, specificity, and positive and negative predictive values for dysplasia optical diagnosis were 70%, 90%, 58% and 94%, respectively. Endoscopic characteristics predictive of dysplasia were: proximal location, loss of innominate lines, polypoid morphology and Kudo pit pattern III–V. Conclusions: CE presents a high diagnostic yield for neoplasia detection, irrespectively of the technology and experience available in any centre. In vivo, CE optical diagnosis is highly accurate for ruling out dysplasia, especially in expert hands. Lesion characteristics can aid the endoscopist for in situ therapeutic decisions. Trial registration number: NCT02543762.